From Code to Creativity: Exploring the Horizons of Artificial Intelligence Content Creation - Palomino-Flores, Paola (2024)
In a world where technology transforms our interaction with reality, this study investigates how Artificial Intelligence (AI) merges logic and creativity in content generation. Beyond algorithms, AI expands the boundaries of human imagination, giving rise to new forms of narrative. The research was conducted through a literature review and sentiment analysis involving 300 participants. The results revealed that AI not only impacts emotions but also combines machine logic with human imagination, surpassing the limits of conventional creativity and raising fundamental questions about authorship in the AI era. Furthermore, it emphasizes the importance of educating both creative professionals and the general public about AI’s capabilities and limitations, as well as the necessity of establishing robust ethical regulatory frameworks and actively promoting collaboration between humans and AI systems.